Sudden Intracranial Hemorrhage in a Patient With Atypical Chronic Myeloid Leukemia in Chronic Phase. Issue 8 (November 2018) - Kouzuki, Kagehiro; Umeda, Katsutsugu; Saida, Satoshi; Kato, Itaru; Hiramatsu, Hidefumi; Funaki, Takeshi; Kanda, Kenji; Muramatsu, Hideki; Yoshida, Kenichi; Ogawa, Seishi; Adachi, Souichi
Abstract : A 16-year-old boy was incidentally found to have hyperleukocytosis during a school physical examination. He was diagnosed with atypical chronic myeloid leukemia in chronic phase. Although treatment with hydoxyurea was started, his white blood cell count increased and he eventually developed lethal intracranial hemorrhage. Although very rare, intracranial hemorrhage should be considered as a possible complication in patients with atypical chronic myeloid leukemia, even in chronic phase, if they have hyperleukocytosis and thrombocytopenia.